Plant Viral Vectors - Palmer, Kenneth; Gleba, Yuri.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
In this volume, the authors provide an excellent overview of how far the plant viral vector field has come. This discipline is no longer exclusively the domain of academics − there is a small, but growing number of small biotechnology companies that exploit plant viruses as a platform for commercial innovation in crop improvement, industrial product manufacturing, and human and veterinary health care.  The authors, who work in the plant viral “vectorology” field, have Bill Dawson to thank in some way for their scientific pedigree, and they are honored that he contributed the opening chapter of this volume with the history of plant virus vector development: “A vector is not a virus; it is a device designed to perform a specific function.” Other contributors have provided fascinating reviews of how plant viral vectors have been adapted to serve specific functions, from plant gene function discovery to nanotechnology, providing infinitely scalable manufacturing systems valuable for human therapeutics. .
Preface -- A personal history of virus-based vector construction by William O. Dawson -- Virus-derived ssDNA vectors for the expression of foreign proteins in plants by Edward P. Rybicki and Darrin P. Martin -- Plant Viral Epitope Display Systems for Vaccine Development by Denis Leclerc -- Applications of plant viruses in bionanotechnology by George P. Lomonossoff and David J. Evans -- Milestones in the development and applications of plant virus vector as gene silencing platforms -- by Christophe Lacomme -- Emerging Antibody-based Products by Kevin J. Whaley, Josh Morton, Steve Hume, Ernie Hiatt, Barry Bratcher, Victor Klimyuk, Andrew Hiatt, Michael Pauly, and Larry Zeitlin -- Production of Recombinant Antigens and Antibodies in Nicotiana benthamiana Using ‘magnifection’ Technology: GMP-Compliant Facilities for Small-and Large-Scale Manufacturing by Victor Klimyuk, Gregory Pogue, Stefan Herz, John Butler, and Hugh Haydon -- Plant viral vectors for delivery by Agrobacterium by Yuri Y. Gleba, Daniel Tusé and Anatoli Giritch -- Subject index.
Keywords: Virology; Vaccines; Virology; Vaccine